From genes to drugs: CYP2C19 and pharmacogenetics in clinical practice - Shubbar, Qamar; Alchakee, Aminah; Issa, Khaled Walid; Adi, Abdul Jabbar; Shorbagi, Ali Ibrahim; Saber-Ayad, Maha (Frontiers in Pharmacology, 2024)
The CYP2C19 gene is frequently included in different pharmacogenomic panels tested in clinical practice, due to its involvement in the metabolism of a myriad of frequently prescribed medications. Accordingly, CYP2C19 genotyping can promote precise therapeutic decisions and avoid the occurrence of significant drug-drug-gene interactions in the clinical setting. A comprehensive examination of the role of the CYP2C19 gene in real-world medical settings is presented in this review. This review summarizes the most recent information on how genetic variants in CYP2C19 affect drug metabolism and therapeutic outcome. It goes into the wide range of CYP2C19 phenotypes, with different degrees of metabolizing activity, and their implications for customized medication response through a review of the literature. The review also analyzes the clinical significance of CYP2C19 in several medical specialties, including cardiology, psychiatry, and gastro-enterology clinics, and illuminates how it affects pharmacological efficacy, safety, and adverse effects. Finally, CYP2C19-supported clinical decision-making is outlined, highlighting the possibility of improving therapeutic outcomes and achieving more affordable treatment options, a step towards optimizing healthcare provision through precision medicine.